Application of AI for Analysis of Historical Collections and Artifacts - Putra, Endry Putra; Desi Swista Dewi, Maria; Suprapto, Agung (Brawijaya University Library, 2024)
The Naga community, a traditional Sundanese group living in Neglasari Village, West Java, utilizes plant diversity, including bamboo, for their daily needs. This research aims to investigate the diversity, utilization, and management of bamboo among the Naga community. The study employs a narrative literature review method focusing on the analysis and synthesis of various relevant literature sources to provide a comprehensive understanding of the topic. There are seven species and varieties of bamboo in the Naga community's gardens, namely Bambusa vulgaris (haur hejo and haur koneng), Gigantochloa apus (awi tali), Gigantochloa pseudoarundinacea (awi gede/awi gombong), Gigantochloa atter (awi temen), Gigantochloa atroviolacea (awi hideung), and Schizostachyum iraten (awi tamiyang). These bamboos are used for various purposes, such as building materials, traditional musical instruments, cooking utensils, and agricultural tools. The Naga community manages bamboo traditionally, which includes land preparation, planting, maintenance, pest control, harvesting, and utilization. These practices have contributed to the conservation of bamboo, essential for the sustainability of their livelihoods. The diverse knowledge and management practices of bamboo by the Naga community highlight the importance of support in preserving their cultural heritage and traditional knowledge. The findings provide insights and recommendations for sustainable bamboo management and conservation in Indonesia and globally. The government and relevant stakeholders are expected to support community conservation efforts by providing access to modern technology and resources